Optimal Hybrid Renewable Energy System Design: A Techno-Economic Analysis Across Diverse Sites - Hossein Kiani; Hossein Gharibvand; Mohammad Hassan Nazari; Gevork B. Gharehpetian; Seyed Hossein Hosseinian (AUT Journal of Electrical Engineering)
Enhancing the efficiency and environmental compatibility of hybrid systems through renewable energy sources is a highly motivating concept. Two tourist destinations, one Sarab Gian region in Nahavand city of Iran and the other in Zurich city in Switzerland, were analyzed. Using HOMER Pro software, photovoltaic panels (PVs), wind turbines (WTs), battery energy storage systems (BESS), and diesel generators (DGs) were evaluated. Sensitivity factors such as varying fossil fuel costs, fuel supply limitations, inflation rates, discount rates, carbon dioxide penalties, and capacity shortages were taken into account. The findings indicate that as fuel prices and emission penalties rise, renewable resources become more cost-effective. Comparing the lowest net present cost (NPC) in Switzerland to Iran, which is also influenced by fuel prices, 180% increase was observed. Furthermore, due to the impact of fuel prices and the optimal capacity of PVs, we observed a 5.3% increase in total operational costs in scenario Sarab Gian (CA) compared to Zurich (CB). Additionally, Switzerland benefits from lower inflation and discount rates, leading to a 19.3% reduction in NPC and a 41% decrease in the cost of energy (COE) compared to Iran. This study emphasizes the economic feasibility of renewable energy in hybrid systems, particularly in regions with high fossil fuel costs and strict emission regulations.